Re-sensitization of Mycobacterium smegmatis to Rifampicin Using CRISPR Interference Demonstrates Its Utility for the Study of Non-essential Drug Resistance Traits - Faulkner, Valwynne; Cox, Adrienne Adele; Goh, Shan; van Bohemen, Annelies; Gibson, Amanda J.; Liebster, Oliver; Wren, Brendan W.; Willcocks, Sam; Kendall, Sharon L. (Frontiers in Microbiology, 2021)
A greater understanding of the genes involved in antibiotic resistance in Mycobacterium tuberculosis is necessary for the design of improved therapies. Clustered regularly interspaced short palindromic repeat interference (CRISPRi) has been previously utilised in mycobacteria to identify novel drug targets by the demonstration of gene essentiality. The work presented here shows that it can also be usefully applied to the study of non-essential genes involved in antibiotic resistance. The expression of an ADP-ribosyltransferase (arr) involved in rifampicin resistance in Mycobacterium smegmatis was silenced using CRISPRi and the impact on rifampicin susceptibility was measured. Gene silencing resulted in a decrease in the minimum inhibitory concentration (MIC) similar to that previously reported in an arr deletion mutant. There is contradictory evidence for the toxicity of Streptococcus pyogenes dCas9 (dCas9Spy) in the literature. In this study the expression of dCas9Spy in M. smegmatis showed no impact on viability. Silencing was achieved with concentrations of the aTc inducer lower than previously described and with shorter induction times. Finally, designing small guide RNAs (sgRNAs) that target transcription initiation, or the early stages of elongation had the most impact on rifampicin susceptibility. This study demonstrates that CRISPRi based gene silencing can be as impactful as gene deletion for the study of non-essential genes and further contributes to the knowledge on the design and induction of sgRNAs for CRISPRi. This approach can be applied to other non-essential antimicrobial resistance genes such as drug efflux pumps